2016
DOI: 10.1186/s13568-015-0175-7
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of PHO13 improves ethanol production via the xylose isomerase pathway

Abstract: Xylose is the second most abundant sugar in lignocellulosic materials and can be converted to ethanol by recombinant Saccharomyces cerevisiae yeast strains expressing heterologous genes involved in xylose assimilation pathways. Recent research demonstrated that disruption of the alkaline phosphatase gene, PHO13, enhances ethanol production from xylose by a strain expressing the xylose reductase (XR) and xylitol dehydrogenase (XDH) genes; however, the yield of ethanol is poor. In this study, PHO13 was disrupted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…This result implied that maintaining a moderate XI activity has a positive effect on the enhancement of xylose fermentation. The overexpression of Xks1p and four enzymes in the non-oxidative PPP is a common strategy to strengthen xylose metabolism (Bamba et al 2016; Kuyper et al 2005a; Peng et al 2012; Sharma et al 2016). Previous reports have shown that moderate, rather than extremely high, Xks1p activity is more beneficial for growth and ethanol production from xylose because this enzyme catalyzes an ATP-consuming reaction (Jin et al 2003; Peng et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result implied that maintaining a moderate XI activity has a positive effect on the enhancement of xylose fermentation. The overexpression of Xks1p and four enzymes in the non-oxidative PPP is a common strategy to strengthen xylose metabolism (Bamba et al 2016; Kuyper et al 2005a; Peng et al 2012; Sharma et al 2016). Previous reports have shown that moderate, rather than extremely high, Xks1p activity is more beneficial for growth and ethanol production from xylose because this enzyme catalyzes an ATP-consuming reaction (Jin et al 2003; Peng et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The chassis cell BSIF was diploid; therefore, to destroy two alleles of PHO13 , which would benefit xylose metabolism (Bamba et al 2016; Lee et al 2014; Shen et al 2012; Van Vleet et al 2008), two plasmids were assembled in the plasmid pUC19 as follows: pXIP1/2 (Additional file 1: Fig. S2a) containing two pairs of PHO13 -targeted recombinant arms, PHO13 - RA1 vs. PHO13 - RA2 and PHO13 - RA1 vs. PHO13 - RA3 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intracellular metabolites were prepared by leakage‐free quenching and cold methanol extraction as previously described and analyzed by liquid chromatography–triple quadrupole mass spectrometry (LC–QqQ‐MS), using (+)‐10‐camphorsulfonic acid as an internal standard, as described by Bamba et al…”
Section: Methodsmentioning
confidence: 99%